Agronomic characteristics of peanut genotypes aiming at precocity - Heuert, Jair (2022)
The present work aimed to evaluate the agronomic characteristics of peanut genotypes, aiming at precocity. The experiment was carried out in the agricultural year 2021/22, in the experimental area of ​​the Peanut Breending Program (PMA) of the Brazilian Agricultural Research Corporation (EMBRAPA) Arroz e Feijão, in the municipality of Santo Antônio de Goiás. A randomized block design with four replications was used. The treatments were twelve genotypes, two cultivars (BRS 421 OL and BRS 423 OL) and ten lines (2173 OL, 2946 OL, 2133 OL, 3226 OL, 2094 OL, 2988 OL, 2055 OL, 1876 OL, 2717 OL and 2991 OL), developed by the WFP. The plots were composed of two lines of three meters in length, spacing between lines of 0.90 m, interval between plots of two meters and a useful plot of 5.4 m2. Mature grains, late leaf spot severity, 100 grain weight and pod yield were evaluated. It is concluded that the BRS 421 OL, 2173 OL and 2946 OL genotypes had the lowest late leaf spot severities. Only 2717 OL and 2173 OL presented grain maturation above 70%. The most productive were 2717 OL, 2946 OL, 2055 OL, BRS 421 OL and 2173 OL, showing yield potential above 5,000 kg ha-1, when harvested at 115 DAP.